1975
DOI: 10.1136/gut.16.8.585
|View full text |Cite
|
Sign up to set email alerts
|

Carnosinase activity of human gastrointestinal mucosa.

Abstract: SUMMARY Carnosinase, the dipeptidase which hydrolyses carnosine and other histidine-containing dipeptides, was assayed in mucosal tissues of the human and of the rat gut. Kinetic properties of the intestinal enzyme were found to be similar to carnosinase of other animal tissues. Little or no activity was detected in human gastric or colonic mucosa, and the levels were lower in duodenal than jejunal mucosa. The distribution of carnosinase is similar to that of the disaccharidases. Mean carnosinase activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Zucker obese rats treated with L-carnosine were less dyslipidemic and exhibited improved renal function in comparison with the control group (Aldini et al, 2011). Unfortunately, such dietary supplementation in human is ineffective due to the presence of L-carnosinase in human gastrointestinal mucosa and other tissues that degrade this dipeptide (Sadikali et al, 1975;Teufel et al, 2003). Studies using N-acetyl cysteine have proven that the strategy of designing and synthesizing pharmaceuticals with better scavenging activity might be feasible (Lasram et al, 2015).…”
Section: Neutralization Of 4-hydroxyalkenalsmentioning
confidence: 93%
“…Zucker obese rats treated with L-carnosine were less dyslipidemic and exhibited improved renal function in comparison with the control group (Aldini et al, 2011). Unfortunately, such dietary supplementation in human is ineffective due to the presence of L-carnosinase in human gastrointestinal mucosa and other tissues that degrade this dipeptide (Sadikali et al, 1975;Teufel et al, 2003). Studies using N-acetyl cysteine have proven that the strategy of designing and synthesizing pharmaceuticals with better scavenging activity might be feasible (Lasram et al, 2015).…”
Section: Neutralization Of 4-hydroxyalkenalsmentioning
confidence: 93%
“…The presence of such effective carnosinase activity in plasma explains why Asatoor et al (1970) and Sadikali et at. (1975) failed to detect carnosine in plasma after carnosine ingestion by humans.…”
Section: Discussionmentioning
confidence: 99%
“…A putative proton-linked peptide carrier has also recently been partially characterized in basolateral membranes, and carnosine inhibited the transport of glycyl-L-proline by it (Dyer, Beechey, Gorvel, Smith, Wootton & CARNOSINE ABSORPTION AND EXCRETION Shirazi-Beechey, 1990). However, carnosinase activity has been identified in the small intestine of several species including humans (Parshin, 1946;Sadikali, Darwish & Watson, 1975) though Parshin (1946) found less activity in human mucosa than in other species, and Hanson & Smith (1949) reported that it was absent from pig intestine though present in pig kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an H + -driven process. Inside the enterocytes, a limited amount of carnosine is hydrolyzed by carnosinase-2 into β-alanine and histidine (Sadikali et al 1975). The intracellular carnosine is exported by peptide/histidine transporters 1 and 2 (PHT1 and PHT2) out of the enterocyte across its basolateral membrane into the lamina propria of the small-intestinal mucosa.…”
Section: Absorption Of Carnosine By the Small Intestine And Transportmentioning
confidence: 99%